2015
DOI: 10.1038/srep08062
|View full text |Cite
|
Sign up to set email alerts
|

Gate-tuned quantum oscillations of topological surface states in β-Ag2Te

Abstract: We report the strong experimental evidence of the existence of topological surface states with large electric field tunability and mobility in β-Ag2Te. Pronounced 2D Shubnikov-de Haas oscillations have been observed in β-Ag2Te nanoplates. A Berry phase is determined to be near π using the Landau level fan diagram for a relatively wide nanoplate while the largest electric field ambipolar effect in topological insulator so far (~2500%) is observed in a narrow nanoplate. The π Berry phase and the evolution of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Figure 5 shows the Seebeck coefficient as a function of the temperature measured from Ag 2 Te nanowire. As previous studies reported that Ag 2 Te is -type semiconductor [1,6,15], the Seebeck coefficient reveals negative values, confirming that the majority of charge carriers are electrons. The Seebeck coefficients also drastically change at 130 ∘ C, similar trend of the resistance.…”
Section: Resultssupporting
confidence: 50%
“…Figure 5 shows the Seebeck coefficient as a function of the temperature measured from Ag 2 Te nanowire. As previous studies reported that Ag 2 Te is -type semiconductor [1,6,15], the Seebeck coefficient reveals negative values, confirming that the majority of charge carriers are electrons. The Seebeck coefficients also drastically change at 130 ∘ C, similar trend of the resistance.…”
Section: Resultssupporting
confidence: 50%
“…We mention here briefly that measurements of the resistance in two different geometries 24 indicated metallic topological surface states 5,8,9 below 100K. Since these are not expected to be a factor in the results presented here, we defer discussion of them to a later paper.…”
Section: B Electronic Transportmentioning
confidence: 80%
“…Topological surface states have been subsequently confirmed experimentally. 8,9 This work was followed by several high-pressure x-ray diffraction studies combined with firstprinciples electronic structure calculations, identifying four phases as the pressure is increased. [10][11][12] Phase I was determined to be semiconducting with topological conducting surface states, transforming into a semi-metallic Phase II through an isostructural transition identified as an electronic topological transition at 1.8-2.0 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was recently shown to have characteristics associated with topologically nontrivial band inversion [8] and that if formed as a 2D crystal it may exhibit topological insulator characteristics [9]. Topological insulator behavior is also well established [10][11][12][13] in Ag 2 Se and Ag 2 Te. However the Cu 2−x Te phase diagram includes structures not fully determined in all cases, and there are several phase transitions at high temperatures [14,15] as the Te lattice adapts to superionic motion of the Cu ions [16].…”
Section: Introductionmentioning
confidence: 99%